Dynamic Navigation vs Freehand Dental Implant Placement: A Systematic Review of Surgical Efficiency and Clinical Outcomes - Muhammad Rizqan; Muhammad Rizqi Maulana Fatah (Indonesian Journal of Case Reports, 2026)
Precise implant positioning is critical for functional, biological, and prosthetic success in dental implant therapy. Dynamic navigation systems provide real-time intraoperative guidance and may enhance placement accuracy compared with conventional freehand techniques. However, their impact on clinical outcomes remains incompletely clarified. To evaluate clinical outcomes, surgical efficiency, and complication rates of dynamic navigation–assisted dental implant placement compared with freehand techniques in adult patients. A systematic search of PubMed, Cochrane Library, and ScienceDirect identified comparative clinical studies evaluating dynamic navigation versus freehand implant placement. Primary outcomes included postoperative pain, operative time, surgical complications, and early implant success. Nine studies were included in the qualitative synthesis. Dynamic navigation consistently demonstrated significantly reduced coronal, apical, and angular deviations compared with freehand placement. Selected studies reported shorter operative times and lower early postoperative pain in navigation groups. Major complications were rare in both techniques, although minor transient neurosensory disturbances were reported more frequently with freehand placement. Early implant survival rates were high and comparable across groups. While dynamic navigation reliably enhances surgical precision and may improve procedural efficiency, its influence on early implant survival appears limited. Improved accuracy may offer greater safety in anatomically complex regions; however, long-term clinical superiority remains uncertain. Dynamic navigation improves implant placement accuracy and may enhance surgical efficiency without increasing complications, but further long-term evidence is needed to establish definitive clinical advantages.